Novel Ionic Liquids for Thermoelectric Generator Devices. (2019) - Laux, Edith; Jeandupeux, Laure; Uhl, Stefanie; Keppner, Herbert; Pérez López, Pilar; Sanglard, Pauline; Vanoli, Ennio; Marti, Roger
Abstract: In recent years, ionic liquids (ILs) have been investigated as thermoelectric materials in thermoelectric generators (TEG). Reduced toxicity, high boiling point, low thermal conductivity at good conductivity are striking properties With thermal conductivities, typically 1/10 th of solid state materials, a small thermal flow can generate a high temperature difference and, with that, a high voltage (or Seebeck coefficient, SE) can be achieved. However, carrier extraction (current) from the liquid to an external load is still an issue and needs further improvement. The creation of the electrode potential could be described by the Nernst equation taking into account the involvement of charged species in the liquid, such as the anions and cations of the IL and the species for the redox couples. In the past, more than 25 ILs were screened, focusing in particular on non-hazardous and environmental friendly ILs, based on amino acids. Most of them show large positive (p-SE). There is, however, a lack of ILs with similar large negative Seebeck coefficients (n-SE) allowing to be joined combined with p-SE cells to better internal resistance matching for output power improvement. In this paper, we show further progress only focusing on finding large n-SE liquids; carrier extraction for TEG-current will not be considered. We argue that the ion attachment at the electrode interface plays a crucial role for high generator voltages. For current extraction, the IL must be "blended" with redox couples, allowing carrier extraction to an external load in a reversible cyclic process and the role of attached ions from ILs may be considered as internally created "bias" . Blending, however, was experienced in the past by our work and others, leads unavoidably to both p- and n-SE reduction. Based on new experiments a first exception was found using Co 2+/3+ (bpy)3 (TFSI2 )2/3 redox couples in combination with choline lactate; it was observed that the n-SE could be increased up to -3630 µV/K, making it a promising candidate for a high performance TEG.